O‐GlcNAcylation regulates β1, 4‐GlcNAc‐branched N‐glycan biosynthesis via the OGT/SLC35A3/GnT‐IV axis. Issue 2 (3rd January 2022) - Song, Wanli; Isaji, Tomoya; Nakano, Miyako; Liang, Caixia; Fukuda, Tomohiko; Gu, Jianguo
Abstract: N ‐Linked glycosylation and O ‐linked N ‐acetylglucosamine ( O ‐GlcNAc) are important protein post‐translational modifications that are orchestrated by a diverse set of gene products. Thus far, the relationship between these two types of glycosylation has remained elusive, and it is unclear whether one influences the other via UDP‐GlcNAc, which is a common donor substrate. Theoretically, a decrease in O ‐GlcNAcylation may increase the products of GlcNAc‐branched N ‐glycans. In this study, via examination by lectin blotting, HPLC, and mass spectrometry analysis, however, we found that the amounts of GlcNAc‐branched tri‐antennary N ‐glycans catalyzed by N ‐acetylglucosaminyltransferase IV (GnT‐IV) and tetra‐antennary N ‐glycans were significantly decreased in O ‐GlcNAc transferase knockdown cells (OGT‐KD) compared with those in wild type cells. We examined this specific alteration by focusing on SLC35A3, which is the main UDP‐GlcNAc transporter in mammals that is believed to modulate GnT‐IV activation. It is interesting that a deficiency of SLC35A3 specifically leads to a decrease in the amounts of GlcNAc‐branched tri‐ and tetra‐antennary N ‐glycans. Furthermore, co‐immunoprecipitation experiments have shown that SLC35A3 interacts with GnT‐IV, but not with N ‐acetylglucosaminyltransferase V. Western blot and chemoenzymatic labeling assay have confirmed that OGT modifies SLC35A3 and that O ‐GlcNAcylation contributes to its stability. Furthermore, we found that SLC35A3‐KO enhances cell spreading and suppresses both cell migration and cell proliferation, which is similar to the phenomena observed in the OGT‐KD cells. Taken together, these data are the first to demonstrate that O ‐GlcNAcylation specifically governs the biosynthesis of tri‐ and tetra‐antennary N ‐glycans via the OGT‐SLC35A3‐GnT‐IV axis.